The need to establish local Diabetes Mellitus registries - Sreedharan, Jayadevan (Nepal Journal of Epidemiology, 2016)
The epidemiologists look at the distribution, determinants and health related states of diseases which will assist in the control of the disease as well as its survival pattern. Disease registries provide information regarding the components of the epidemiology of that particular disease.